Polyacrylonitrile-based carbon fiber precursor as well as preparation method and application thereof
By controlling the coefficient of swelling of the thermally drafted fibers and optimizing the spinneret hole density during the wet spinning process, combining multi-stage bundling and post-treatment steps, the problems of large differences in fiber monofilament properties and many wool filaments are solved, and the quality and performance of carbon fiber raw filaments are improved.
Patent Information
- Application Number
- CN202311348536.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-18
AI Technical Summary
In the prior art, the problem of large differences in fiber monofilament properties and many wool filaments during wet spinning process affects the performance of carbon fiber composite materials.
By controlling the coefficient of swelling of the thermally drafted fibers, the optimized pore density of the spinneret and the control of the solidification process are used, and the polyacrylonitrile-based carbon fiber raw silk is prepared by controlling the expansion coefficient of the thermally drafted fibers.
It effectively reduces the difference in properties of monofilaments, reduces the generation of wool filaments, and improves the quality of carbon fiber filaments and the performance of final carbon fiber.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon fiber, and in particular to a polyacrylonitrile-based carbon fiber precursor and a preparation method and application thereof. Background Art
[0002] Carbon fiber is a fibrous material mainly composed of carbon elements. Compared with general materials, in addition to having inherent characteristics such as low density, high temperature resistance, friction resistance, electrical conductivity, thermal conductivity and corrosion resistance, carbon fiber has the structural characteristics of preferential orientation of turbostratic graphite crystallites along the fiber axis, which makes it have high strength and modulus along the fiber axis. Carbon fiber is a composite material made of skeleton structure, and its specific strength and specific modulus are still the highest among existing engineering materials. In addition to its relatively soft characteristics, various composite material structures made by carbon fiber winding and weaving processes can be used in high-end manufacturing fields such as aerospace, hydrogen storage cylinders, and wind power blades.
[0003] Since carbon fiber composites are formed by impregnating bundled carbon fibers with resin, the inherent characteristics of the tow are important factors affecting the performance of the composite. In theory, the fibers in the tow should have relatively consistent characteristics, but in fact, since each single filament in the industrially produced tow is located in the same position, it is inevitable that there are differences in various mass transfer and heat transfer conditions between the single filaments during the forming process. From the physical morphology alone, there is a 1-5% difference in the thickness of the single filaments. Obviously, this difference has a significant impact on the performance of the final composite material. The generally accepted conclusion is that the defects in the original filament will be inherited to the carbon fiber, and the various defects of the carbon fiber tow will be inherited to the composite material, so it is very important to avoid the difference system from the source.
[0004] Patent applications CN201710777381.8, CN201780041618.4, CN201880057751.3, CN202122194771.7 and CN202110590805.6 have studied and reported the uniformity problems in the stock solution preparation step, coagulation step, steam drawing step, sizing step, and composite material forming step during the fiber forming process, and provided optimization solutions. It can be found that no matter at which stage, large variability and poor uniformity of monofilaments caused by any factors mean a loss of tensile strength of the final product. Therefore, all kinds of properties of monofilaments in high-strength tows must be uniform. It is clear that the consistency of monofilaments not only refers to the consistency in physical form, but also requires good consistency in secondary structures such as crystallization, pores, and skin-core structures of high-quality raw fibers. This consistency requires that the monofilaments undergo the same process during the production process, that is, the central control indicators for the monofilaments cannot deviate significantly. This includes the uniformity control of polymerization, steam drawing, sizing, composite forming and other links mentioned in the literature. However, there is still a lack of research on the uniformity of fiber control indicators in the hot water drawing process during fiber production. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of large differences in properties of fiber monofilaments and many hairy fibers in wet spinning in the prior art, and to provide a polyacrylonitrile-based carbon fiber precursor and a preparation method and application thereof.
[0006] In order to achieve the above object, the present invention provides a method for preparing polyacrylonitrile-based carbon fiber precursor, the method comprising the following steps:
[0007] (1) spinning and coagulating the spinning solution, and then hot drawing to obtain hot drawn fibers;
[0008] (2) post-treating the heat-drawn fibers to obtain polyacrylonitrile-based carbon fiber precursors;
[0009] Wherein, the coefficient of variation of swelling degree of the heat-drawn fiber is ≤5%.
[0010] Preferably, the degree of swelling of the heat-drawn fiber is 80-120%.
[0011] Preferably, the single filament fineness of the heat-drawn fiber is 1-4 Dtex.
[0012] Preferably, the hole density of the spinneret used in spinning is 80-200 holes / cm2, preferably 120-160 holes / cm2;
[0013] Preferably, the spinneret used in spinning is a circular spinneret.
[0014] Preferably, the width of the spun fibers obtained by controlled coagulation is 0.8-1.1 cm / k.
[0015] Preferably, the number of stages of the heat drawing is 3-5.
[0016] Preferably, the method also includes a bundling process before each stage of hot stretching, and the width of the filaments after each bundling satisfies the following relationship: 0.8A / Dr≥B≥1.1A / Dr; wherein B is the width of the filaments after this bundling, A is the width of the filaments after the previous bundling, and Dr is the stretching multiple of this stage of hot stretching.
[0017] Preferably, the bundling is performed at a distance of 5-10 cm from the entrance of the hot water drawing tank.
[0018] Preferably, the temperature of the hot stretching is 80-98° C., and the temperature of each stage of stretching is not lower than the temperature of the previous stage of stretching.
[0019] Preferably, the total multiple of the thermal stretching is 2-6 times.
[0020] Preferably, the post-treatment process includes: washing, oiling, drying and densification, steam drawing and heat setting.
[0021] The second aspect of the present invention provides polyacrylonitrile-based carbon fiber precursor prepared by the method described above.
[0022] The third aspect of the present invention provides the use of the polyacrylonitrile-based carbon fiber precursor described above in the preparation of carbon fiber.
[0023] A fourth aspect of the present invention provides a method for preparing carbon fiber, the method comprising the following steps:
[0024] The polyacrylonitrile-based carbon fiber precursor described above is subjected to pre-oxidation, low-temperature carbonization and high-temperature carbonization.
[0025] Preferably, the pre-oxidation temperature is 200-260°C;
[0026] Preferably, the temperature of the low-temperature carbonization is 400-750°C;
[0027] Preferably, the high temperature carbonization temperature is 1150-1450°C.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention provides a method for preparing polyacrylonitrile carbon fiber precursor, which can produce carbon fiber precursor with small difference in single-filament properties and less fuzz by controlling the coefficient of variation of swelling of hot-drawn fibers.
[0030] 2. In the method described in the present invention, by optimizing the hole density of the spinneret, controlling the width of the primary fiber and the degree of shrinkage during the hot drawing process, the uniformity of mass transfer, heat transfer and deformation during the fiber forming process is improved, the difference between the single fiber structures during the carbon fiber precursor forming process is reduced, and the quality of the obtained carbon fiber precursor is further improved. DETAILED DESCRIPTION
[0031] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0032] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] The inventors of the present invention found during the research process that in the preparation process of polyacrylonitrile carbon fiber precursor, swelling is an important central control indicator in the precursor production process. At present, the swelling is usually only monitored on the average value. In the actual research process, the inventors found that there is a strong correlation between the coefficient of variation of the swelling of the obtained hot-drawn fiber and the final carbon fiber performance. Controlling the coefficient of variation of the swelling can improve the uniformity of the fiber monofilaments, reduce the adverse effects caused by the differences between the monofilaments, and thus help to obtain better quality carbon fiber. Based on this, the present invention was completed.
[0034] In one aspect, the present invention provides a method for preparing polyacrylonitrile-based carbon fiber precursor, the method adopts a wet spinning process, and the method comprises the following steps:
[0035] (1) spinning and coagulating the spinning solution, and then hot drawing to obtain hot drawn fibers;
[0036] (2) post-treating the heat-drawn fibers to obtain polyacrylonitrile-based carbon fiber precursors;
[0037] Wherein, the coefficient of variation of swelling degree of the heat-drawn fiber is ≤5%.
[0038] In a preferred embodiment, the spinning solution contains a polyacrylonitrile copolymer and a solvent.
[0039] In a preferred embodiment, the intrinsic viscosity of the polyacrylonitrile copolymer is 1.5-2.8 dL / g.
[0040] In a preferred embodiment, the concentration of the polyacrylonitrile copolymer in the spinning solution is 19-21% by weight.
[0041] More preferably, the polyacrylonitrile copolymer is obtained by copolymerizing acrylonitrile and a second monomer, wherein the second monomer is selected from monomers containing a vinyl group.
[0042] Further preferably, the second monomer is selected from itaconic acid or polymethyl methacrylate
[0043] In a specific embodiment, when the second monomer is selected from an acidic monomer such as itaconic acid, before the spinning solution is spun, the method further comprises the step of treating the spinning solution with ammonia gas, which can neutralize the carboxyl groups in itaconic acid.
[0044] In a preferred embodiment, the content of the acrylonitrile structural unit in the polyacrylonitrile copolymer is ≥95% by weight, and the content of the second monomer structural unit is ≥0.6% by weight. Further preferably, the content of the acrylonitrile structural unit in the polyacrylonitrile copolymer is 95-99.4% by weight, and the content of the second monomer structural unit is 0.6-5% by weight.
[0045] In a preferred embodiment, the solvent may be dimethyl sulfoxide.
[0046] In a preferred embodiment, the spinneret used in spinning is a circular spinneret.
[0047] In the wet spinning process, if the spinneret hole density is too large, the mass transfer difference in the forming process will become larger. At this time, the solvent concentration inside the spinneret is too high, which makes the swelling degree of the coagulated primary fiber higher; while the spinneret hole density is low, it will cause uneven spinneret pressure during large-diameter spinning, causing the fiber fineness variation to become larger. Based on this, in order to further improve the uniformity of the heat-drawn fiber filaments, the coefficient of variation of the filament swelling degree is reduced. The hole density of the spinneret needs to be reasonably controlled. In a preferred embodiment, the hole density of the spinneret used during spinning is 80-200 holes / square centimeter, preferably 120-160 holes / square centimeter.
[0048] More preferably, the number of holes in the spinneret is 1000-12000, and the hole diameter is 0.04-0.08 mm.
[0049] In a preferred embodiment, the coagulation bath used during coagulation is a dimethyl sulfoxide aqueous solution, and more preferably, the concentration of dimethyl sulfoxide in the coagulation bath is 45-82 weight %; specifically, it can be 45 weight %, 50 weight %, 55 weight %, 60 weight %, 65 weight %, 70 weight %, 75 weight %, 80 weight % or 82 weight %.
[0050] In a preferred embodiment, the temperature of the coagulation bath is 25-35°C; specifically, it can be 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 32°C, 34°C or 35°C.
[0051] In the method of the present invention, if the width is too narrowed when leaving the coagulation bath, the outer fibers cannot be bundled immediately and then adhere to the roller surface under the action of surface tension, resulting in broken fibers. Based on this, in order to further improve the uniformity of the hot-drawn fiber monofilaments and reduce the coefficient of variation of the monofilament swelling, the width of the spun fibers obtained after coagulation can be reasonably controlled. Preferably, the width of the spun fibers obtained by coagulation (i.e., the width of the spun fibers at the coagulation outlet) is 0.8-1.1 cm / k.
[0052] In a preferred embodiment, the heat drawing stage is 3-5 stages.
[0053] In the present invention, during the hot drawing process, as the fibers become thinner, the width needs to be continuously narrowed. If the degree of narrowing is insufficient, split filaments and hairy filaments are easily generated, while if the width of the narrowing is too large, uneven stretching will be caused by increased thickness. Therefore, in order to further improve the uniformity of the hot-drawn fiber filaments and reduce the structural differences in the fiber forming process, the degree of narrowing during the hot drawing process can be reasonably controlled. In a preferred embodiment, the method also includes a process of bundling before each stage of hot drawing; and the width of the filaments after each bundling satisfies the following relationship: 0.8A / Dr≥B≥1.1A / Dr; wherein B is the width of the filaments after this bundling, in cm / k, A is the width of the filaments after the previous bundling, in cm / k, and Dr is the drafting multiple of the current stage of hot drawing; wherein, when the first bundling is performed, the width of the filaments after the previous bundling refers to the width of the filaments at the solidification outlet.
[0054] In a specific embodiment, when the number of hot drawing stages is 3, the specific process of step (1) includes: spinning and coagulating the spinning solution, then performing the first bundling and the first stage of hot drawing, then performing the second bundling and the second stage of hot drawing, then performing the third bundling and the third stage of hot drawing to obtain hot drawn fiber; and the width of the filaments after each bundling satisfies the following relationship: 0.8A / Dr≥B≥1.1A / Dr, and the width of the filaments after each bundling satisfies the following relationship: 0.8A / Dr≥B≥1.1A / Dr; wherein B is the width of the filaments after this bundling, in cm / k, A is the width of the filaments after the previous bundling, in cm / k, and Dr is the stretching multiple of this stage of hot drawing. For example, when the width of the filaments at the coagulation outlet (i.e., the width of the spun fibers obtained by coagulation) is 0.9 cm / k, and the draw ratio of the first-stage hot drawing is 1.3, the width of the filaments after the first bundle is
[0055] In the present invention, the filament width refers to the characteristic of the fiber bundle thickness. During the spinning process, fibers are always manufactured in bundles, and the filament bundle is usually flat during the running process. Although the filament width is width data, due to the use of different spinneret specifications, a comprehensive consideration should be given when making a lateral comparison. Therefore, the filament width characteristic described in the present invention adopts the width ratio number method (cm / k) to reflect the stacking state of the filament bundle during the running process.
[0056] In a preferred embodiment, the bundling is performed at a distance of 5-10 cm from the entrance of the hot water drawing tank.
[0057] In a preferred embodiment, the hot stretching is performed in a hot water stretching tank.
[0058] In a preferred embodiment, the temperature of the hot stretching is 80-98° C., and the temperature of each stage of stretching is not lower than the temperature of the previous stage of stretching.
[0059] In a preferred embodiment, the total multiple of the thermal stretching is 2-6 times.
[0060] In the present invention, the coefficient of variation of the swelling of the heat-drawn fiber represents the difference in swelling between the fiber monofilaments. The inventors of the present invention found during the research process that if the difference in swelling between the fiber monofilaments is large, even if the difference in swelling eventually disappears after drying, the structural characteristics of the original fiber that cause the difference in swelling will not disappear, and the differences in crystallization, pores, and skin-core structure in the original fiber structure are inherited. When subsequent oxidation and carbonization are performed, this structural difference will be further amplified. This leads to a large discrete coefficient of performance of a single fiber, resulting in a decrease in the quality of the carbon fiber. In addition, due to the large difference in swelling, it will cause an increase in hairy fibers, further deteriorating the fiber quality. Based on this, the method described in the present invention reasonably controls the coefficient of variation of the swelling of the heat-drawn fiber, thereby improving the quality of the carbon fiber and reducing the generation of hairy fibers.
[0061] In a preferred embodiment, the coefficient of variation of fiber swelling can be detected by the following method:
[0062] (1) Place the sample to be tested in an ultrafiltration centrifuge tube and centrifuge at a centrifugal force of 5000 g for 6 min. Manually separate the fibers and randomly select 10 groups of fiber samples, each with 10 single fibers;
[0063] (2) Test the swelling degree of each group of fibers separately. The swelling degree test process is as follows: weigh the sample to be tested and record it as W3, then dry the fiber and weigh it as W4, swelling degree = 100*(W3-W4) / W4;
[0064] (3) Calculate the standard deviation SD and mean MN of the swelling degree of 10 groups of fiber samples, and then calculate the coefficient of variation Cv according to the following formula: Cv = (SD / MN) × 100%.
[0065] In the present invention, in the test method for the coefficient of variation of swelling of the above-mentioned fibers, each group of samples is composed of 10 single fibers during sampling, which can not only accurately and intuitively reflect the test results of swelling difference, but also reduce the inconvenience caused by the weighing process due to the light weight of a single fiber.
[0066] In a preferred embodiment, the degree of swelling of the heat-drawn fiber is 80-120%, more preferably 90-110%; specifically, it can be 80%, 85%, 90%, 95%, 100%, 105%, 110%, 115% or 120%.
[0067] In a preferred embodiment, the coefficient of variation of swelling of the heat-drawn fiber is ≤4%.
[0068] In a preferred embodiment, the single filament fineness of the heat-drawn fiber is 1-4 Dtex.
[0069] In a preferred embodiment, the post-treatment process includes: washing, oiling, drying and densification, steam drawing and heat setting.
[0070] In a specific embodiment, there are no special requirements for the conditions of water washing, oiling, drying and densification, steam drawing and heat setting, and they can be conventional conditions in the art.
[0071] In a specific embodiment, the oil agent used for oiling is amino silicone oil.
[0072] In a specific embodiment, the drying and densification temperature is 110-150°C; specifically, it can be 110°C, 120°C, 130°C, 140°C or 150°C.
[0073] In a specific implementation manner, the steam stretching pressure is 200-350 KPa, and the stretching multiple is 2 times.
[0074] In a specific embodiment, the pressure during heat setting is 80-180 KPa.
[0075] In the present invention, pressure refers to absolute pressure.
[0076] In the method described in the present invention, by reasonably controlling the plate density of the spinneret and the width of the primary fiber obtained by coagulation, and reasonably controlling the degree of shrinkage in the hot drawing process, hot-drawn fibers with good structural consistency are obtained; after further processing, polyacrylonitrile and carbon fiber precursors are obtained.
[0077] The second aspect of the present invention provides polyacrylonitrile-based carbon fiber precursor prepared by the method described above.
[0078] The third aspect of the present invention provides the use of the polyacrylonitrile-based carbon fiber precursor described above in the preparation of carbon fiber.
[0079] A fourth aspect of the present invention provides a method for preparing carbon fiber, the method comprising the following steps:
[0080] The polyacrylonitrile-based carbon fiber precursor described above is subjected to pre-oxidation, low-temperature carbonization and high-temperature carbonization.
[0081] Preferably, the pre-oxidation temperature is 200-260°C.
[0082] Preferably, the temperature of the low-temperature carbonization is 400-750°C.
[0083] Preferably, the high temperature carbonization temperature is 1150-1450°C.
[0084] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.
[0085] The characterization and testing methods used in the following examples and comparative examples are as follows:
[0086] 1. Test method for swelling degree of hot drawn fiber: Take 5g of the sample to be tested, place it in an ultrafiltration centrifuge tube and centrifuge it at a centrifugal force of 5000g for 6 minutes, take it out, weigh it and record it as W1, then dry the fiber and weigh it as W2.
[0087] Swelling degree = 100*(W1-W2) / W2
[0088] 2. Test method for coefficient of variation of swelling of hot drawn fibers:
[0089] (1) Place the sample to be tested in an ultrafiltration centrifuge tube and centrifuge at a centrifugal force of 5000 g for 6 min. Manually separate the fibers and randomly select 10 groups of fiber samples, each with 10 single fibers;
[0090] (2) Test the swelling degree of each group of fibers separately. The swelling degree test process is as follows: weigh the sample to be tested and record it as W3, then dry the fiber and weigh it as W4, swelling degree = 100*(W3-W4) / W4;
[0091] (3) Calculate the standard deviation SD and mean MN of the swelling degree of 10 groups of fiber samples, and then calculate the coefficient of variation (Cv) according to the following formula:
[0092] Cv=(SD / MN)×100%.
[0093] 3. Carbon fiber tensile strength test method, refer to the method described in GB / T 3362-2005.
[0094] Example 1
[0095] (1) The spinning stock solution is a 20 wt % polyacrylonitrile copolymer dimethyl sulfoxide solution, the intrinsic viscosity of the polyacrylonitrile copolymer is 1.88 dL / g, the polyacrylonitrile copolymer contains 98.5 wt % acrylonitrile structural units and 1.5 wt % itaconic acid structural units, and NH3 is introduced before spinning to neutralize the carboxyl groups; the spinning stock solution is passed through a circular spinneret (with 6 k holes, a hole diameter of 0.060 mm, and a plate hole density of 150 holes / cm 2 ) is extruded into a coagulation bath (60 wt % dimethyl sulfoxide aqueous solution, temperature is 35°C), and the filament width at the coagulation outlet is controlled to be 1 cm / k; then the first bundling and the first stage hot drawing are carried out, and the filament width after the first bundling is 0.77 cm / k, the temperature of the first stage hot drawing is 90°C, and the drawing ratio is 1.3 times; then the second bundling and the second stage hot drawing are carried out, and the filament width after the second bundling is 0.59 cm / k, the temperature of the second stage hot drawing is 92°C, and the drawing ratio is 1.3 times; then the third bundling and the third stage hot drawing are carried out, and the third stage hot drawing is carried out. After three bundles, the width of the yarn is 0.46 cm / k, the temperature of the third-level hot drawing is 94°C, and the drawing ratio is 1.3 times; then the fourth bundle and the fourth-level hot drawing are carried out, and the width of the yarn after the fourth bundle is 0.35 cm / k, the temperature of the fourth-level hot drawing is 95°C, and the drawing ratio is 1.3 times; the bundle is carried out at a distance of 10 cm from the entrance of the hot water drawing tank, and the total width after the fourth-level hot drawing is 2.1 cm, the swelling degree of the hot-drawn fiber is 95%, the swelling degree variation coefficient of the hot-drawn fiber is 3.1%, and the single yarn fineness is 1.6 Dtex;
[0096] (2) After the heat-drawn fiber is washed with water, the fiber is coated with amino silicone oil and dried at 140°C for densification, then steam-drawn by 2 times at 350 KPa and heat-set at 150 KPa to obtain polyacrylonitrile carbon fiber precursor.
[0097] The polyacrylonitrile carbon fiber precursor is pre-oxidized at 200-240°C, low-temperature carbonized at 700°C, and high-temperature carbonized at 1350°C to obtain a carbon fiber product with no hair, a tensile strength of 5.61 GPa, and a Young's modulus of 315 KPa.
[0098] Example 2
[0099] (1) The spinning stock solution is a 20 wt % polyacrylonitrile copolymer dimethyl sulfoxide solution, the intrinsic viscosity of the polyacrylonitrile copolymer is 1.88 dL / g, the polyacrylonitrile copolymer contains 98.5 wt % acrylonitrile structural units and 1.5 wt % itaconic acid structural units, and NH3 is introduced before spinning to neutralize the carboxyl groups; the spinning stock solution is passed through a circular spinneret (with 6 k holes, a hole diameter of 0.060 mm, and a plate hole density of 140 holes / cm 2 ) is extruded into a coagulation bath (60 wt % dimethyl sulfoxide aqueous solution, temperature is 35°C), and the width of the filament at the coagulation outlet is controlled to be 1 cm / k; then the first bundling and the first stage hot drawing are carried out. After the first bundling, the width of the filament is 0.77 cm / k, the temperature of the first stage hot drawing is 90°C, and the drawing ratio is 1.3 times; then the second bundling and the second stage hot drawing are carried out. After the second bundling, the width of the filament is 0.57 cm / k, the temperature of the second stage hot drawing is 92°C, and the drawing ratio is 1.35 times; then the third bundling and 3-stage hot drawing, after the third bundling, the width of the filament is 0.41cm / k, the temperature of the 3-stage hot drawing is 94°C, and the drawing ratio is 1.4 times; then the fourth bundling and 4-stage hot drawing are carried out, the width of the filament after the fourth bundling is 0.29cm / k, and the drawing ratio is 1.4 times; bundling is carried out at a distance of 10cm from the entrance of the hot water drawing tank, and the total width after four stages of drawing is 1.74cm, the swelling degree of the hot drawn fiber is 90%, the swelling degree variation coefficient of the hot drawn fiber is 2.8%, and the single yarn fineness is 1.5Dtex.
[0100] (2) After the heat-drawn fiber is washed with water, the fiber is coated with amino silicone oil and dried at 140°C for densification, then steam-drawn by 2 times at 350 KPa and heat-set at 150 KPa to obtain polyacrylonitrile carbon fiber precursor.
[0101] The polyacrylonitrile carbon fiber precursor is pre-oxidized at 200-240°C, low-temperature carbonized at 700°C, and high-temperature carbonized at 1200-1300°C to obtain a carbon fiber product with no hair, a tensile strength of 5.75 GPa, and a Young's modulus of 307 KPa.
[0102] Example 3
[0103] (1) The spinning stock solution is a 20 wt % polyacrylonitrile copolymer dimethyl sulfoxide solution, the intrinsic viscosity of the polyacrylonitrile copolymer is 1.88 dL / g, the polyacrylonitrile copolymer contains 98.5 wt % acrylonitrile structural units and 1.5 wt % itaconic acid structural units, and NH3 is introduced before spinning to neutralize the carboxyl groups; the spinning stock solution is passed through a circular spinneret (with 6 k holes, a hole diameter of 0.060 mm, and a plate hole density of 140 holes / cm 2) is extruded into a coagulation bath (60 wt % dimethyl sulfoxide aqueous solution, temperature is 35°C), and the filament width at the coagulation outlet is controlled to be 0.8 cm / k; then the first bundling and the first-stage hot drawing are carried out, and the filament width after the first bundling is 0.59 cm / k, the temperature of the first-stage hot drawing is 90°C, and the drawing ratio is 1.35 times; then the second bundling and the second-stage hot drawing are carried out, and the filament width after the second bundling is 0.44 cm / k, the temperature of the second-stage hot drawing is 92°C, and the drawing ratio is 1.35 times; then the third bundling and the third-stage hot drawing are carried out, After the third bundling, the width of the yarn is 0.31 cm / k, the temperature of the 3rd level hot drawing is 94°C, and the drawing ratio is 1.4 times; then the fourth bundling and 4th level hot drawing are carried out, and the width of the yarn after the fourth bundling is 0.22 cm / k, the temperature of the 4th level hot drawing is 95°C, and the drawing ratio is 1.45 times; bundling is carried out at 10 cm away from the entrance of the hot water drawing tank. After four levels of hot drawing, the total width is 1.30 cm, the swelling degree of the hot drawn fiber is 80%, the swelling degree variation coefficient of the hot drawn fiber is 2.6%, and the single yarn fineness is 1.4Dtex.
[0104] (2) After the hot-drawn fibers were washed with water, they were coated with amino silicone oil and dried at 140°C for densification. They were then drawn twice at 350 KPa and heat-set at 150 KPa to obtain polyacrylonitrile carbon fiber precursors.
[0105] The polyacrylonitrile carbon fiber precursor is pre-oxidized at 200-240°C, low-temperature carbonized at 700°C, and high-temperature carbonized at 1200-1300°C to obtain a carbon fiber product with no hair, a tensile strength of 5.83 GPa, and a Young's modulus of 309 KPa.
[0106] Example 4
[0107] (1) The spinning stock solution is a 20 wt % polyacrylonitrile copolymer dimethyl sulfoxide solution, the intrinsic viscosity of the polyacrylonitrile copolymer is 1.88 dL / g, the polyacrylonitrile copolymer contains 98.5 wt % acrylonitrile structural units and 1.5 wt % itaconic acid structural units, and NH3 is introduced before spinning to neutralize the carboxyl groups; the spinning stock solution is passed through a circular spinneret (with 6k holes, 0.060 mm hole diameter, and 60 holes / cm plate hole density) 2) is extruded into a coagulation bath (60 wt % dimethyl sulfoxide aqueous solution, temperature is 35°C), the filament width at the coagulation outlet is controlled to be 1 cm / k, and then the first bundling and the first stage hot drawing are carried out. After the first bundling, the filament width is 0.38 cm / k, the temperature of the first stage hot drawing is 90°C, and the drawing ratio is 1.1 times; then the second bundling and the second stage hot drawing are carried out. After the second bundling, the filament width is 0.28 cm / k, the temperature of the second stage hot drawing is 92°C, and the drawing ratio is 1.1 times; then the third bundling and the third stage hot drawing are carried out, and the third After the first bundling, the width of the yarn is 0.20cm / k, the temperature of the third-level hot drawing is 94°C, and the drawing ratio is 1.1 times; then the fourth bundling and the fourth-level hot drawing are carried out, the width of the yarn after the fourth bundling is 0.15cm / k, the temperature of the fourth-level hot drawing is 95°C, and the drawing ratio is 1.2 times; bundling is carried out at a distance of 10cm from the entrance of the hot water drawing tank, and the total width after the fourth-level drawing is 3.76cm, the swelling degree of the hot-drawn fiber is 140%, the swelling degree variation coefficient of the hot-drawn fiber is 3.8%, and the single yarn fineness is 4.8Dtex;
[0108] (2) After the hot-drawn fibers were washed with water, they were coated with amino silicone oil and dried at 140°C for densification. They were then drawn twice at 350 KPa and heat-set at 150 KPa to obtain polyacrylonitrile carbon fiber precursors.
[0109] The polyacrylonitrile carbon fiber precursor is pre-oxidized at 200-240°C, low-temperature carbonized at 700°C, and high-temperature carbonized at 1200-1300°C to produce a carbon fiber product with less carbon fiber filaments, a tensile strength of 5.31 GPa, and a Young's modulus of 294 GPa.
[0110] Comparative Example 1
[0111] (1) The spinning stock solution is a 20 wt % polyacrylonitrile copolymer dimethyl sulfoxide solution, the intrinsic viscosity of the polyacrylonitrile copolymer is 1.88 dL / g, the polyacrylonitrile copolymer contains 98.5 wt % acrylonitrile structural units and 1.5 wt % itaconic acid structural units, and NH3 is introduced before spinning to neutralize the carboxyl groups; the spinning stock solution is passed through a circular spinneret (with 6 k holes, a hole diameter of 0.060 mm, and a plate hole density of 240 holes / cm 2) is extruded into a coagulation bath (60 wt % dimethyl sulfoxide aqueous solution, temperature is 35°C), and the filament width at the coagulation outlet is controlled to be 1 cm / k; then the first bundling and the first level of hot drawing are carried out, and the filament width after the first bundling is 0.77 cm / k, the temperature of the first level of hot drawing is 90°C, and the drawing ratio is 1.3 times; then the second bundling and the second level of hot drawing are carried out, and the filament width after the second bundling is 0.59 cm / k, the temperature of the second level of hot drawing is 92°C, and the drawing ratio is 1.3 times; then the third bundling and the third level of hot drawing are carried out, and the filament width after the third bundling is 0.46 cm / k, the temperature of the third level of hot drawing is 94°C, and the drawing ratio is 1.3 times; then the fourth The fiber width after the fourth bundling is 0.35 cm / k, the temperature of the fourth hot drawing is 95°C, and the drawing ratio is 1.3 times; the bundling is carried out at a distance of 10 cm from the entrance of the hot water drawing tank, and the fiber width after each bundling satisfies the following relationship: 0.8A / Dr≥B≥1.1A / Dr; wherein B is the fiber width after this bundling, in cm / k, A is the fiber width after the previous bundling, in cm / k, and Dr is the drawing ratio of this level of hot drawing; after four levels of hot drawing, the total width is 2.1 cm, the fiber swelling degree after hot drawing is 95%, the swelling degree variation coefficient of the hot drawn fiber is 8.5%, and the single fiber fineness is 1.5 Dtex.
[0112] (2) After the hot-drawn fibers were washed with water, they were coated with amino silicone oil and dried at 140°C for densification. They were then drawn twice at 350 KPa and heat-set at 150 KPa to obtain polyacrylonitrile carbon fiber precursors.
[0113] The polyacrylonitrile carbon fiber precursor is pre-oxidized at 200-240°C, low-temperature carbonized at 700°C, and high-temperature carbonized at 1200-1300°C to obtain a carbon fiber product with less lint, a tensile strength of 5.25 GPa, and a Young's modulus of 311 KPa.
[0114] Comparative Example 2
[0115] (1) The spinning stock solution is a 20 wt % polyacrylonitrile copolymer dimethyl sulfoxide solution, the intrinsic viscosity of the polyacrylonitrile copolymer is 1.88 dL / g, the polyacrylonitrile copolymer contains 98.5 wt % acrylonitrile structural units and 1.5 wt % itaconic acid structural units, and NH3 is introduced before spinning to neutralize the carboxyl groups; the spinning stock solution is passed through a circular spinneret (with 6 k holes, a hole diameter of 0.060 mm, and a plate hole density of 140 holes / cm 2) is extruded into a coagulation bath (60 wt % dimethyl sulfoxide aqueous solution, temperature is 35°C), and the filament width at the coagulation outlet is controlled to be 0.5 cm / k; then the first bundling and the first stage hot drawing are carried out, and the filament width after the first bundling is 0.38 cm / k, the temperature of the first stage hot drawing is 90°C, and the drawing ratio is 1.3 times; then the second bundling and the second stage hot drawing are carried out, and the filament width after the second bundling is 0.28 cm / k, the temperature of the second stage hot drawing is 92°C, and the drawing ratio is 1.35 times; then the third bundling and the third stage hot drawing are carried out, and the third stage hot drawing is carried out. After three bundlings, the width of the yarn is 0.20 cm / k, the temperature of the 3rd level hot drawing is 94°C, and the drawing ratio is 1.4 times; then the fourth bundling and 4th level hot drawing are carried out, and the width of the yarn after the fourth bundling is 0.15 cm / k, the temperature of the 4th level hot drawing is 95°C, and the drawing ratio is 1.4 times; bundling is carried out at 10 cm away from the entrance of the hot water drawing tank. After four levels of drawing, the total width is 0.87 cm, the swelling degree of the fiber after hot drawing is 90%, the coefficient of variation of the swelling degree of the fiber after hot drawing is 10.5%, and the single yarn fineness is 1.5 Dtex.
[0116] (2) After the hot-drawn fibers were washed with water, they were coated with amino silicone oil and dried at 140°C for densification. They were then drawn twice at 350 KPa and heat-set at 150 KPa to obtain polyacrylonitrile carbon fiber precursors.
[0117] The polyacrylonitrile carbon fiber precursor is pre-oxidized at 200-240°C, low-temperature carbonized at 700°C, and high-temperature carbonized at 1200-1300°C to obtain a carbon fiber product with less lint, a tensile strength of 5.25 GPa, and a Young's modulus of 311 KPa.
[0118] Comparative Example 3
[0119] (1) The spinning stock solution is a 20 wt % polyacrylonitrile copolymer dimethyl sulfoxide solution, the intrinsic viscosity of the polyacrylonitrile copolymer is 1.88 dL / g, the polyacrylonitrile copolymer contains 98.5 wt % acrylonitrile structural units and 1.5 wt % itaconic acid structural units, and NH3 is introduced before spinning to neutralize the carboxyl groups; the spinning stock solution is passed through a circular spinneret (with 6k holes, 0.060 mm hole diameter, and 60 holes / cm plate hole density) 2) is extruded into a coagulation bath (60 wt % dimethyl sulfoxide aqueous solution, temperature is 35°C), and the filament width at the coagulation outlet is controlled to be 1 cm / k; then the first bundling and the first-stage hot drawing are carried out, and the filament width after the first bundling is 0.38 cm / k, the temperature of the first-stage hot drawing is 90°C, and the drawing ratio is 1.3 times; then the second bundling and the second-stage hot drawing are carried out, and the filament width after the second bundling is 0.28 cm / k, the temperature of the second-stage hot drawing is 92°C, and the drawing ratio is 1.3 times; then the third bundling and the third-stage hot drawing are carried out, After the third bundling, the width of the yarn is 0.20 cm / k, the temperature of the third-level hot drawing is 94°C, and the drawing ratio is 1.3 times; then the fourth bundling and the fourth-level hot drawing are carried out, and the width of the yarn after the fourth bundling is 0.15 cm / k, the temperature of the fourth-level hot drawing is 95°C, and the drawing ratio is 1.3 times; bundling is carried out at a distance of 10 cm from the entrance of the hot water drawing tank, and the total width after the fourth-level drawing is 0.87 cm, the swelling degree of the hot-drawn fiber is 90%, the swelling degree variation coefficient of the hot-drawn fiber is 9.4%, and the single yarn fineness is 1.5 Dtex;
[0120] (2) After the hot-drawn fibers were washed with water, they were coated with amino silicone oil and dried at 140°C for densification. They were then drawn twice at 350 KPa and heat-set at 150 KPa to obtain polyacrylonitrile carbon fiber precursors.
[0121] The polyacrylonitrile carbon fiber precursor is pre-oxidized at 200-240°C, carbonized at 700°C, and carbonized at 1200-1300°C to produce a carbon fiber product with more carbon fiber filaments, a tensile strength of 4.99 GPa, and a Young's modulus of 311 KPa.
[0122] Comparative Example 4
[0123] (1) The spinning stock solution is a 20 wt % polyacrylonitrile copolymer dimethyl sulfoxide solution, the intrinsic viscosity of the polyacrylonitrile copolymer is 1.88 dL / g, the polyacrylonitrile copolymer contains 98.5 wt % acrylonitrile structural units and 1.5 wt % itaconic acid structural units, and NH3 is introduced before spinning to neutralize the carboxyl groups; the spinning stock solution is passed through a circular spinneret (with 6k holes, 0.060 mm hole diameter, and 60 holes / cm plate hole density) 2) is extruded into a coagulation bath (60 wt % dimethyl sulfoxide aqueous solution, temperature is 35°C), and the filament width at the coagulation outlet is controlled to be 1 cm / k; then the first bundling and the first stage hot drawing are carried out, and the filament width after the first bundling is 0.77 cm / k, the temperature of the first stage hot drawing is 90°C, and the drawing ratio is 1.3 times; then the second bundling and the second stage hot drawing are carried out, and the filament width after the second bundling is 0.77 cm / k, the temperature of the second stage hot drawing is 92°C, and the drawing ratio is 1.3 times; then the third bundling and the third stage hot drawing are carried out, and the third After the first bundling, the width of the yarn is 0.77 cm / k, the temperature of the third-level hot drawing is 94°C, and the drawing ratio is 1.3 times; then the fourth bundling and the fourth-level hot drawing are carried out, the width of the yarn after the fourth bundling is 0.77 cm / k, the temperature of the fourth-level hot drawing is 95°C, and the drawing ratio is 1.3 times; bundling is carried out at a distance of 10 cm from the entrance of the hot water drawing tank, and the total width after the fourth-level drawing is 4.62 cm, the swelling degree of the hot-drawn fiber is 90%, the swelling degree variation coefficient of the hot-drawn fiber is 5.21%, and the single yarn fineness is 1.5 Dtex;
[0124] (2) After the hot-drawn fibers were washed with water, they were coated with amino silicone oil and dried at 140°C for densification. They were then drawn twice at 350 KPa and heat-set at 150 KPa to obtain polyacrylonitrile carbon fiber precursors.
[0125] The polyacrylonitrile carbon fiber precursor is pre-oxidized at 200-240°C, carbonized at 700°C, and carbonized at 1200-1300°C to produce a carbon fiber product with more carbon fiber filaments, a tensile strength of 5.21 GPa, and a Young's modulus of 315 KPa.
[0126] Test Example 1
[0127] The fuzziness, tensile strength and Young's modulus of the carbon fibers prepared in the examples and comparative examples are shown in Table 1.
[0128] Table 1
[0129] serial number Hair condition Tensile strength(GPa) Young's modulus(KPa) Example 1 none 5.61 315 Example 2 none 5.75 307 Example 3 none 5.83 309 Example 4 few 5.31 294 Comparative Example 1 few 5.25 311 Comparative Example 2 few 5.11 305 Comparative Example 3 many 4.99 311 Comparative Example 4 many 5.21 315
[0130] As can be seen from Table 1, the method described in the present invention can be used to prepare high-quality carbon fiber precursor without hairy or broken fibers, and the carbon fiber precursor can be used to prepare carbon fiber with excellent performance.
[0131] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing polyacrylonitrile-based carbon fiber precursor, characterized in that: The method comprises the following steps: (1) spinning and coagulating the spinning solution, and then hot drawing to obtain hot drawn fibers; (2) post-treating the heat-drawn fibers to obtain polyacrylonitrile-based carbon fiber precursors; Wherein, the coefficient of variation of swelling degree of the heat-drawn fiber is ≤5%.
2. The method according to claim 1, characterized in that The swelling degree of the heat-drawn fiber is 80-120%.
3. The method according to claim 1 or 2, characterized in that: The single filament fineness of the heat-drawn fiber is 1-4 Dtex.
4. The method according to claim 1, characterized in that: The hole density of the spinneret used in spinning is 80-200 holes / cm2, preferably 120-160 holes / cm2; Preferably, the spinneret used in spinning is a circular spinneret.
5. The method according to claim 1, characterized in that The width of the nascent fibers obtained by controlled coagulation is 0.8-1.1 cm / k.
6. The method according to claim 1, characterized in that The heat drawing stage is 3-5 stages.
7. The method according to claim 6, characterized in that The method also includes a bundling process before each stage of hot stretching, and the width of the filaments after each bundling satisfies the following relationship: 0.8A / Dr≥B≥1.1A / Dr; wherein B is the width of the filaments after this bundling, A is the width of the filaments after the previous bundling, and Dr is the stretching multiple of the current stage of hot stretching.
8. The method according to claim 7, characterized in that The bundling is carried out at a distance of 5-10 cm from the entrance of the hot water drawing tank.
9. The method according to claim 1 or 8, characterized in that: The temperature of the hot stretching is 80-98° C., and the temperature of each stage of stretching is not lower than the temperature of the previous stage of stretching.
10. The method according to claim 1 or 8, characterized in that: The total multiple of the thermal stretching is 2-6 times.
11. The method according to any one of claims 1 to 9, characterized in that: The post-treatment process includes: washing, oiling, drying and densification, steam drawing and heat setting.
12. Polyacrylonitrile-based carbon fiber precursor prepared by the method according to any one of claims 1 to 11.
13. Use of the polyacrylonitrile-based carbon fiber precursor according to claim 12 in the preparation of carbon fiber.
14. A method for preparing carbon fiber, characterized in that: The method comprises the following steps: The polyacrylonitrile-based carbon fiber precursor according to claim 12 is subjected to pre-oxidation, low-temperature carbonization and high-temperature carbonization.
15. The method according to claim 14, characterized in that The pre-oxidation temperature is 200-260°C; Preferably, the temperature of the low-temperature carbonization is 400-750°C; Preferably, the high temperature carbonization temperature is 1150-1450°C.
Citation Information
Patent Citations
A method for efficient defoaming and concentration improvement in the polymerization process of carbon fiber production
CN107510958B
Method to uniformly debundle and evenly distribute high fiber count carbon tow
CN109476145A
Sizing agent for reinforcing fibers, and use thereof
CN111051604A
Three-dimensional wet spinning solidification forming system for carbon fiber precursors
CN113279072A
Device for improving steam drafting uniformity of polyacrylonitrile carbon fiber precursor
CN215976163U